Pengaruh Massa Adsorben Arang Aktif Sekam Padi dan Ampas Kopi dalam Mereduksi Zat Pencemar Limbah Cair Indrustri Tempe Rumahan - Sari Zulhija; Alricha Alricha; Moh Baitullah Amaludin; Zeffitni Zeffitni; Sriyati Ramadani (Jurnal Teknologi Berkelanjutan, 2025)
The home-based tempeh industry faces serious challenges in managing liquid waste containing pollutants such as Total Suspended Solid (TSS), ammonia, turbidity, and pH that exceed quality standards. This study aims to determine the decrease in pollutant levels in tempeh industry liquid waste with a combination of coffee grounds and rice husk adsorbents, and to determine the effect of giving variations in adsorbent mass on the value of pollutant parameters in tempeh industry liquid waste. The method used was quantitative experimental with waste samples from Monas Tempe Factory. The adsorbent mass variations tested were 1:1, 1:2, and 2:1, with a total dose of 8 grams per 500 ml of waste, and the adsorption process was carried out with magnetic stirring for 30 minutes at 300 rpm. The results showed that the adsorbent combination was effective in reducing TSS and ammonia, with the highest TSS reduction reaching 53.42% and ammonia 67.33% in the 1:2 variation. The maximum adsorption capacity for TSS was 4330 mg/g and for ammonia 127.50 mg/g. However, this treatment also caused an increase in turbidity (-19937.50%) and pH (-16.88%). The Freundlich isotherm model is more suitable to explain the adsorption process, indicating that adsorption is favorable and occurs physically with multilayer. Although this combination was effective in reducing TSS and ammonia, there were limitations in dealing with turbidity and pH.